Temperature and frequency dependence of AC electrical properties of Zn and Ni doped CoFe2O4 nanocrystals. Issue 19 (3rd July 2017) - Mandal, S. K.; Singh, Swati; Dey, P.; Roy, J. N.; Mandal, P. R.; Nath, T. K.
Abstract: We have investigated the structure and the electrical properties of CoFe2 O4, Ni0.5 Co0.5 Fe2 O4 and Zn0.5 Co0.5 Fe2 O4 nanoparticles, prepared through a chemical pyrophoric reaction technique. The study of the dielectric constant reveals evidence of Rabinkin and Novikova polarisation in the system. The increased value of the dielectric constant at low frequency is attributed to the presence of interfacial and dipolar polarisation in the system. The impedance for Zn0.5 Co0.5 Fe2 O4 nanoparticles is found to decrease with increase in temperature, indicating the presence of a temperature-dependent electrical relaxation process in the system. Nyquist plots have been fitted using parallel combinations of grain boundaries resistance and grain boundaries capacitance. The activation energy is estimated from Nyquist plots, dc and ac conductivity data using the Arrhenius relation. This is indicating that the same type of charge carrier is responsible for the relaxation and the conduction processes in the system. Ac conductivity curves follow a double power law, as proposed by Jonscher. The conduction mechanism with temperature is mainly due to the large polaronic hopping in the system.